World Health Organization risk drinking level reductions are associated with improved functioning and are sustained among patients with mild, moderate and severe alcohol dependence in clinical trials in the United States and United Kingdom - Witkiewitz, Katie; Heather, Nick; Falk, Daniel E.; Litten, Raye Z.; Hasin, Deborah S.; Kranzler, Henry R.; Mann, Karl; O'Malley, Stephanie S.; Anton, Raymond F. (Addiction, 2020)
Aims To examine whether World Health Organization (WHO) risk-level reductions in drinking were achievable, associated with improved functioning and maintained over time among patients at varying initial alcohol dependence severity levels. Design and setting Secondary data analysis of multi-site randomized clinical trials: the US Combined Pharmacotherapies and Behavioral Interventions for Alcohol Dependence (COMBINE) study and the UK Alcohol Treatment Trial (UKATT). Participants Individuals with alcohol dependence enrolled in COMBINE (n = 1383; 68.8% male) and seeking treatment for alcohol problems in UKATT (n = 742; 74.1% male). Interventions Naltrexone, acamprosate or placebo, and combined behavioral intervention or medication management in COMBINE. Social behavior network therapy or motivational enhancement therapy in UKATT. Measurements WHO risk-level reductions were assessed via the calendar method. Alcohol dependence was measured by the Alcohol Dependence Scale, the Leeds Dependence Questionnaire and the Diagnostic and Statistical Manual of Mental Disorders. Measures of functioning included alcohol-related consequences (Drinker Inventory of Consequences and Alcohol Problems Questionnaire), mental health (Short Form Health Survey) and liver enzyme tests. Findings One- and two-level reductions in WHO risk levels in the last month of treatment were maintained at the 1-year follow-up [adjusted odds ratio (OR), 95% confidence interval (CI) = one-level reduction in COMBINE: 3.51 (2.73, 4.29) and UKATT: 2.65 (2.32, 2.98)] and associated with fewer alcohol-related consequences [e.g. B, 95% CI = one-level reduction COMBINE: -26.22 (-30.62, -21.82)], better mental health [e.g. B, 95% CI = one-level reduction UKATT: 9.53 (7.36, 11.73)] and improvements in γ-glutamyltransferase [e.g. B, 95% CI = one-level reduction UKATT: -89.77 (-122.50, -57.04)] at the end of treatment, even among patients with severe alcohol dependence. Results were similar when abstainers were excluded. Conclusions Reductions in World Health Organization risk levels for alcohol consumption appear to be achievable, associated with better functioning and maintained over time in both the United States and the United Kingdom.